Work effectively with your chief financial officer for success in changing environment. Issue 4 (December 2014) - Hope, Joan
<x xml:space="preserve">Abstract</x> KAREN GOLDSTEIN, EXECUTIVE SEARCH CONSULTANT, WITT/KIEFFER